Gelagat kepatuhan zakat perniagaan dalam kalangan perusahaan kecil dan sederhana (PKS) mikro di Wilayah Persekutuan Kuala Lumpur - Marlina, Mat Jais (2021)
Zakat is an obligation for every independent Muslim, to give away zakat for earning above a certain threshold within a certain period of time. Among of the categories in zakat, business zakat collection are still not come along with the rapid growth of the small and medium enterprises (SMEs) Micro in Federal Territory of Kuala Lumpur. Therefore, these study is to identify zakat compliance behaviour among the SMEs business (Micro) in the Federal Territory of Kuala Lumpur. Three main objectives highlighted from these study is to investigate business zakat compliance among the SMEs (Micro). Firstly, to identify the level of attitude, subjective norms, zakat knowledge, perception of zakat distribution, customer satisfaction, credibility of pusat zakat and role of amil zakat. Secondly, to identify the influence of the seven factors on business zakat compliance intention, and thirdly, to identify the effect of the zakat compliance intention on its behaviour. Theory of Planned Behaviour (TPB) used for establishing the research framework. 401 questionnaires were analysed using multiple regressions. Five independent variables influencing business zakat compliance intention are attitude, subjective norms, zakat distribution perception, pusat zakat credibility and zakat amil role (R² = 0.494). Out of three, only two showed significant regression relationship values called credibility of pusat zakat and role of zakat amil. In contrast, the customer satisfaction variable found no significant regression of the zakat payer’s compliance behavioral intentions. Its behaviour is affected by it intention (R² = 0.299). Overall, the six variables play an important role in business zakat compliance behaviour with three new variables added which will be pointed in the next studies. Each result need to be emphasis by zakat authority in order to find the solutions to the SMEs business (Micro) zakat compliance issues in the Federal Territory of Kuala Lumpur